Improving team integration in Malaysian IBS construction projects: A partnering approach - Abdul Nifa, Faizatul Akmar (UUM College of Business, 2012)
Due to the combination of problems and issues that arose using traditional construction methods, such as fragmentation, time delay, wastages, lack of sustainability etc, the Malaysian Government proposed a new solution through industrialisation technology called Industrialised Building System (IBS). Although IBS was introduced over 40 years ago, with well-documented benefits and strong support from the Government, the pace of implementation and usage of IBS is still slow and below Government targets.Investigation by some researchers identified that one of the main barriers of IBS implementation in the Malaysian construction industry is related to poor integration and communication among stakeholders involved during the design stage.A number of reports challenged the construction industry to create a fully integrated process capable of delivering predictable results to clients through processes and team integration.Responding to the challenge, this research hopes to answer this problem and help towards the betterment of the IBS Malaysian construction industry using a partnering approach.The partnering approach is being advocated by many literatures as the solution to the many problems in the construction industry. Therefore, this paper will review the need of integrated team practice, define the concepts of partnering within scope of construction project, is followed by a discussion of the application of partnering in Malaysian IBS projects.It based on the thorough review of the relevant literature within the scope of partnering and Industrialised Building System (IBS).In the end, this paper suggests for the enhancement is needed in term of the level of integration and communication within the construction team and processes for the future research.